PENGARUH PENGGUNAAN DRAW ME GAME TERHADAP KEMAMPUAN SISWA DALAM MENGUASAI KOSAKATA DI SMP NEGERI 3 GUNUNGSITOLI UTARA - Harefa, Trisman; Telaumbanua, Arisman (Jurnal Suluh Pendidikan, 2024)
This study aims to identify the effect of using the Draw Me Game on students' vocabulary mastery in the eighth grade at SMP Negeri 3 Gunungsitoli Utara. The research employs a quasi-experimental design and uses multiple-choice tests as the instrument. Based on the data analysis, the study concludes that the implementation of the Draw Me Game in the experimental class at SMP Negeri 3 Gunungsitoli Utara yielded significant results. Students in the experimental class showed a clear improvement in their vocabulary skills, with average post-test scores categorized as good after the treatment. In contrast, the control class, which did not receive the treatment, exhibited less significant results, with average scores remaining in the poor category. Statistical testing confirms that the Draw Me Game has a positive and significant effect on students' vocabulary mastery, indicating that this method is effective in enhancing students' learning achievements.